2017
DOI: 10.1155/2017/5469597
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Perturbation and Potential Markers in Patients with Esophageal Cancer

Abstract: Clinical diagnosis of esophageal cancer (EC) at early stage is rather difficult. This study aimed to profile the molecules in serum and tissue and identify potential biomarkers in patients with EC. A total of 64 volunteers were recruited, and 83 samples (24 EC serum samples, 21 serum controls, 19 paired EC tissues, and corresponding tumor-adjacent tissues) were analyzed. The gas chromatography time-of-flight mass spectrometry (GC/TOF-MS) was employed, and principal component analysis was used to reveal the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
(28 reference statements)
2
15
0
Order By: Relevance
“…5A) showed that of the 38 up-regulated metabolites in ZD:CTRL esophagus, about 1/3 (32%) were associated with metabolic alteration in amino acid (AA) metabolism. Differences in AA levels have been reported in many human cancers, including ESCC (35,36,40). Six AAs (lysine, histidine, proline, serine, tyrosine, glycine) are similarly up-regulated in human ESCC (36).…”
Section: Zd:ctrl Rat Esophagus Exhibits a Tumor-associated Metabolomementioning
confidence: 88%
See 1 more Smart Citation
“…5A) showed that of the 38 up-regulated metabolites in ZD:CTRL esophagus, about 1/3 (32%) were associated with metabolic alteration in amino acid (AA) metabolism. Differences in AA levels have been reported in many human cancers, including ESCC (35,36,40). Six AAs (lysine, histidine, proline, serine, tyrosine, glycine) are similarly up-regulated in human ESCC (36).…”
Section: Zd:ctrl Rat Esophagus Exhibits a Tumor-associated Metabolomementioning
confidence: 88%
“…Metabolomics analysis showed that the ESCC-bearing ZD:CTRL esophagus has a highly dysregulated metabolome, with 69 significantly altered metabolites. In particular, ∼32% of the up-regulated metabolites are implicated in active amino acid biosynthesis, a common feature of human ESCC (35,36,40). Phosphoenolpyruvate, the top down-regulated species in ZD:CTRL vs. ZS:CTRL esophagus (−5.83-fold, P = 0.010), is a metabolic checkpoint of antitumor T cell responses (47).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics (of which lipidomics is a branch), is a promising field of systems biology that investigates the sets of metabolites and lipids present in biological systems. Therefore, metabolomics and lipidomics have been used to study the biomarkers of many human diseases, including esophageal cancer (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In this study, through primary screening of sensitive cancer cell lines, esophageal cancer was selected, and an untargeted lipidomic analysis based on an LC-MS/MS analysis of clinical samples (blood plasma samples from healthy volunteers and esophageal cancer patients, tumor tissues and paracancerous tissues from esophageal cancer patients), were performed to identify candidate lipid biomarkers in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol levels are higher in EC tissues compared to corresponding tumor-adjacent tissues [15]. To the best of our knowledge, few reports are available about the role of SCAP or cholesterol in the metastasis of EC.…”
Section: Introductionmentioning
confidence: 91%